Orange juice containing Pediococcus acidilactici CE51 modulates the intestinal microbiota and reduces induced inflammation in a murine model of colitis - de Oliveira Vieira, Karolinny Cristiny; da Silva, Ana Beatriz Batista; Felício, Suelen Aparecida; Lira, Fábio Santos [UNESP]; de Figueiredo, Caíque [UNESP]; Bezirtzoglou, Eugenia; Pereira, Valéria Cataneli; Nakagaki, Wilson Romero; Nai, Gisele Alborghetti; Winkelströter, Lizziane Kretli (Springer Nature, 2023)
The management of inflammatory bowel diseases has been widely investigated, especially ulcerative colitis. Thus, studies with the application of new probiotic products are needed in the prevention/treatment of these clinical conditions. The objective of this work was to evaluate the effects of probiotic orange juice containing Pediococcus acidilactici CE51 in a murine model of colitis. 45 male Swiss lineage mice were used, divided into five groups (n = 9): control, colitis, colitis + probiotic (probiotic orange juice containing CE51), colitis + placebo (orange juice) and colitis + sulfasalazine (10 mg/kg/Weight). The induction of colitis was performed with dextran sodium sulfate (3%). The treatment time was 5 and 15 days after induction. Histopathological analysis, serum measurements of TNF-α and C-reactive protein and metagenomic analysis of feces were performed after euthanasia. Probiotic treatment reduced inflammation in the small intestine, large intestine and spleen. The probiotic did not alter the serum dosages of TNF-α and C-reactive protein. Their use maintained the quantitative ratio of the phylum Firmicutes/Bacteroidetes and increased Lactobacillus helveticus with 15 days of treatment (p < 0.05). The probiotic orange juice containing P. acidilactici CE51 positively modulated the gut microbiota composition and attenuated the inflammation induced in colitis.